2018
DOI: 10.1155/2018/3082893
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Changes in Retinal Thickness in Type 2 Diabetes without Diabetic Retinopathy

Abstract: Objective To examine the changes in retinal thickness of patients with diabetes without DR. Designs A randomization, crossover, retrospective practice. Participants 43 diabetic patients and 43 ethnic-, age-, and sex-matched controls. Methods Full retinal thicknesses of ten areas were assessed using spectral domain optical coherence tomography. Confounding variables, such as age, gender, and glycated haemoglobin (HbA1c) level, were assessed by regression analysis. Main Outcome Measures Mean retinal thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…Therefore, at an early stage of DR, reduced RLT may be an important morphological change, indicating neurodegeneration. In fact, such changes in diabetic retinas have been detected by optical coherence tomography (OCT) [33]. In accordance with these observations, in the current study, we observed greater retinal cell apoptosis, consequently causing significant thinning of various layers of the retina in STZ-induced diabetic rats compared to normal rats.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, at an early stage of DR, reduced RLT may be an important morphological change, indicating neurodegeneration. In fact, such changes in diabetic retinas have been detected by optical coherence tomography (OCT) [33]. In accordance with these observations, in the current study, we observed greater retinal cell apoptosis, consequently causing significant thinning of various layers of the retina in STZ-induced diabetic rats compared to normal rats.…”
Section: Discussionsupporting
confidence: 90%
“…The thickness at one to seven grids of six macular neuroretinal layers and RPE in patients without diabetic neuropathy was significantly thinner than those in controls. However, the influence of diabetes on the thickness of the macular neuroretinal layers had not been consistent (8,29), because OCT image quality depends on the instrument reliability and measurement variability (30). SS-OCT uses 1 µ wavelength light source, allowing deeper penetration into the photoreceptors and RPE (31).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum macular thickness is found within the 3 mm diameter of the parafovea, while the thinnest retina is observed in the temporal retina decreasing gradually toward the periphery [51]. This relative thinness of temporal retina beyond the center 3 mm of the macula may contribute to greater vulnerability to ischemia and hence diabetic changes [52]. Wide-field fluorescein angiography appears to also support this increased susceptibility of the temporal midperipheral retina to diabetic changes.…”
Section: Within-subject Faz Area Enlargementsmentioning
confidence: 90%